Phylogenetic classification of human papillomavirus genotypes in high-grade cervical intraepithelial neoplasia in women from a densely populated Brazilian urban region - Pitta, Denise Rocha; Sarian, Luis Otávio; Campos, Elisabete Aparecida; Rabelo-Santos, Sílvia Helena; Syrjänen, Kari; Derchain, Sophie Françoise (São Paulo Medical Journal, 2009)
CONTEXT AND OBJECTIVE: Differences in human papillomavirus (HPV) types may correlate with the biological potential and invasion risk of high-grade cervical intraepithelial neoplasia (CIN 2 and CIN 3). The objective of this study was to determine the relationship between different combinations of HPV types and CIN severity. DESIGN AND SETTING: Cross-sectional study, at Universidade Estadual de Campinas (Unicamp). METHODS: Cervical samples from 106 women treated due to CIN 2 (18) or CIN 3 (88) were examined for specific HPV genotypes using Roche Linear Array® (LA-HPV). The proportions of CIN 2 and CIN 3 in groups of women infected with the HPV phylogenetic groups A7 and A9 were compared. Three groups were formed: women with single infections; multiple infections; and the whole sample. RESULTS: Multiple infections were detected in 68 samples (64.7%). The most frequent high-risk genotypes detected (single/multiple) were HPV 16 (57.1%), HPV 58 (24.7%), HPV 33 (15.2%), HPV 52 (13.3%), HPV 31 (10.4%), HPV 51 (7.6%) and HPV 18 (6.6%). Women without infection with HPV species Alpha 9 were less likely to have CIN 3 than were their Alpha 9 HPV-infected counterparts. HPV 16 and/or HPV 18, with or without associations with other viral types, were more frequently found in women with CIN 3 than in those with CIN 2. CONCLUSIONS: The severity of high-grade CIN may be aggravated by the presence of HPV types included in the Alpha 9 phylogenetic classification and by infections including HPV 16 and 18, singly or in combination with other HPV genotypes.